Structures and Free Energy Landscapes of the Wild-Type and A30P Mutant-Type α-Synuclein Proteins with Dynamics - Wise-Scira, Olivia (American Chemical Society, 2013)
[Image: see text] The genetic missense A30P mutation of the wild-type α-synuclein protein results in the replacement of the 30th amino acid residue from alanine (Ala) to proline (Pro) and was initially found in the members of a German family who developed Parkinson’s disease. Even though the structures of these proteins have been measured before, detailed understanding about the structures and their relationships with free energy landscapes is lacking, which is of interest to provide insights into the pathogenic mechanism of Parkinson’s disease. We report the secondary and tertiary structures and conformational free energy landscapes of the wild-type and A30P mutant-type α-synuclein proteins in an aqueous solution environment via extensive parallel tempering molecular dynamics simulations along with thermodynamic calculations. In addition, we present the residual secondary structure component transition stabilities at the atomic level with dynamics in terms of free energy change calculations using a new strategy that we reported most recently. Our studies yield new interesting results; for instance, we find that the A30P mutation has local as well as long-range effects on the structural properties of the wild-type α-synuclein protein. The helical content at Ala18-Gly31 is less prominent in comparison to the wild-type α-synuclein protein. The β-sheet structure abundance decreases in the N-terminal region upon A30P mutation of the wild-type α-synuclein, whereas the NAC and C-terminal regions possess larger tendencies for β-sheet structure formation. Long-range intramolecular protein interactions are less abundant upon A30P mutation, especially between the NAC and C-terminal regions, which is linked to the less compact and less stable structures of the A30P mutant-type rather than the wild-type α-synuclein protein. Results including the usage of our new strategy for secondary structure transition stabilities show that the A30P mutant-type α-synuclein tendency toward aggregation is higher than the wild-type α-synuclein but we also find that the C-terminal and NAC regions of the A30P mutant-type α-synuclein are reactive toward fibrillzation and aggregation based on atomic level studies with dynamics in an aqueous solution environment. Therefore, we propose that small molecules or drugs blocking the specific residues, which we report herein, located in the NAC- and C-terminal regions of the A30P mutant-type α-synuclein protein might help to reduce the toxicity of the A30P mutant-type α-synuclein protein.